Pembentukan Karakter Kemandirian Siswa melalui Implementasi Full Day School di SDIT Kreatif Makkah Padang - Nurkhasanah, Ani Fitria; Kosim, Muhammad (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to: 1) Understand the implementation of the formation of students' independent character through the implementation of the full day school program at SDIT Creative Makkah Padang. 2) Knowing the supporting factors in forming students' independent character through the full day school program at SDIT Creative Makkah Padang. 3) Knowing the factors inhibiting the formation of students' independent character through the full day school program at SDIT Creative Makkah Padang. The research method used in this research is a qualitative method with a descriptive approach supported by data collection techniques in the form of interviews with 6 teaching staff, observations at school and data obtained from various literature such as books, journals and other related sources. The results of the research show that: 1) The formation of students' independent character is carried out with a curriculum by including tahfidz in the daily study schedule and the formation of personality character through habituation activities by carrying out dhuha prayers and obligatory noon and asr prayers in congregation. 2) Supporting factors in the formation of independent character are strong commitment from all parties who take part in cultivating student character, clear and structured planning of each activity, support and cooperation from teachers and parents. 3) Obstacles to the formation of independent character values are the different backgrounds and characters of students.